Measuring the peak performance of a 6G THz communication testbed - Smith, J. F.; Gui, Y.; Fatadin, I. (Frontiers in Antennas and Propagation, 2024)
It is expected that 6G communication technology will achieve a peak data rate capability of 1 Tbit/s. One way of reaching this goal is to employ THz frequencies for carrying wireless signals. THz frequencies have large continuous bandwidths which allow for high data rate signals. In order to support the development of THz communications and accompanying technologies, a 6G THz Communications Testbed has been set-up at the National Physical Laboratory. In this paper, the best signal performance for a variety of different baud rates and modulation schemes is explored for both a direct connection between the waveform generator and measuring oscilloscope and for several different Over-The-Air (OTA) path lengths up to 4m specular Non-Line-of-Sight. For the direct connection, signals of up to 210 Gbit/s were achieved and data rates of up to 150 Gbit/s were achieved for OTA transmission.